Internal-Control Willingness and Managerial Overconfidence - Liu, Bin; Li, Lin (Frontiers in Psychology, 2021)
Internal Control is a branch of accounting subject, and accounting control and risk management are the core of enterprise internal control. Previous studies have shown that high-quality internal control inhibits or regulates managerial overconfidence. However, it is believed that the influential factors of internal-control quality are normally objective factors, such as corporate characteristics, financial status, and governance structure. Corresponding to another type of constituent elements, that is, the subjective factor, which we call internal-control willingness, has not been explored. In the study, we define internal-control willingness as the degrees of subjective initiative of the internal-control construction and execution activities of enterprises. And we propose a method to measure internal-control willingness based on text analysis and machine learning by Python, then we test its impact on internal-control quality. Moreover, we test the impact of internal-control willingness on managerial overconfidence. Our findings: (A) internal-control willingness has a positive impact on internal-control quality, and (B) internal-control willingness lowers managerial overconfidence. Our study introduces subjective initiative factor into the field of internal control, and also extends the understanding of internal-control theory. Based on empirical conclusions, we suggest regulatory authorities and corporate boards improve incentive mechanisms to jointly strengthen internal-control willingness of all employees, so as to help enterprise managers operate rationally.